The beneficial effects of curcumin in cirrhotic rats with portal hypertension - Hsu, Shao-Jung (Biosci Rep, 2017)
In liver cirrhosis with portal hypertension, the uneven distribution of vasoactive substances leads to increased intrahepatic vascular resistance and splanchnic vasodilatation. Angiogenesis also induces increased portal inflow and portosystemic collaterals. The collaterals may induce lethal complications such as gastroesophageal variceal hemorrhage, but the therapeutic effect of vasoconstrictors is still suboptimal due to poor collateral vasoresponsivenss. Curcumin has aroused much attention for its antifibrosis, vasoactive, and anti-angiogenesis actions. However, whether it affects the aforementioned aspects is unknown. Liver cirrhosis was induced by common bile duct ligation (CBDL) in Sprague–Dawley rats. Sham-operated rats were controls. CBDL and sham rats were randomly allocated to receive curcumin (600 mg/kg per day) or vehicle since the 15th day after BDL. On the 29th day, portal hypertension related parameters were surveyed. Portosystemic collateral in situ perfusion was performed to evaluate vascular activity. Chronic curcumin treatment decreased portal pressure (PP), cardiac index (CI) and increased systemic vascular resistance (SVR) in cirrhotic rats. In splanchnic system, curcumin decreased superior mesenteric artery (SMA) flow and increased SMA resistance. Mesenteric angiogenesis was attenuated by curcumin. Acute administration of curcumin significantly induced splanchnic vasoconstriction. The mesenteric protein expressions of p-endothelial nitric oxide synthase (eNOS), cyclooxygenase (COX) 2 (COX2), vascular endothelial growth factor (VEGF), p-VEGF receptor 2 (VEGFR2), and p-Erk were down-regulated. In collateral system, curcumin decreased portosystemic shunting and induced vasoconstriction. In conclusion, chronic curcumin administration in cirrhotic rats ameliorated portal hypertension related hemodynamic derangements and portosystemic collaterals. Curcumin also attenuated splanchnic hyperdynamic circulation by inducing vasoconstriction through inhibition of eNOS activation and by decreasing mesenteric angiogenesis via VEGF pathway blockade.